Education demand in tertiary institutions: an empirical assessment of international students’ demand in Ghana. - Aboagye, Ebenezer Asare (KNUST, 2025)
A Dissertation Submitted In Partial Fulfillment Of The Requirements For Master Of Science In Economics.